Flow cytometric characterization of tumor subpopulations in three sublines of the dunning R3327 rat prostate tumor model - Glowa, Christin; Peschke, Peter; Karger, Christian; Hahn, Eric W.; Huber, Peter E.; Debus, Jürgen; Ehemann, Volker (The prostate, 2013)
BACKGROUND Subsets of tumor cells were characterized by mapping DNA ploidy patterns in correlation with established cell surface markers in three non-treated sublines of the Dunning R3327 prostate tumor system representing different progressional stages. METHODS Flow cytometry was used to analyze DNA-index, cell cycle distribution as well as multiparametric aquisition of single and combined cell surface markers in single cell suspensions of frozen tumor tissues. RESULTS The three Dunning prostate tumor sublines clearly differ in their ploidy status. In addition each tumor subline displays a characteristic cell surface marker profile, which is correlated with the cell cycle phase and the amount of genomic alterations. CONCLUSIONS In a feasibility study we have shown that cross-reacting antibodies to human cell surface markers stain discrete tumor subpopulations in three sublines of the Dunning tumor model. Although it remains presently uncertain, which cell surface markers are most suitable for cell sorting to display cancer initiating (CIC) properties following subcutaneous or orthotopic grafting, the model may be useful for mechanistic investigations of putative stem-like tumor subpopulations and their significance in response to radio- or chemotherapy. Prostate 73: 1710-1720, 2013. © 2013 Wiley Periodicals, Inc.